Impacts of iodoacetic acid on reproduction: current evidence, underlying mechanisms, and future research directions - Mei Ha; Li Mou; Jiayuan Qu; Changjiang Liu (Frontiers Media S.A., 2024)
In light of the undeniable and alarming fact that human fertility is declining, the harmful factors affecting reproductive health are garnering more and more attention. Iodoacetic acid (IAA), an emerging unregulated drinking water disinfection byproduct, derives from chlorine disinfection and is frequently detected in the environment and biological samples. Humans are ubiquitously exposed to IAA daily mainly through drinking water, consuming food and beverages made from disinfected water, contacting swimming pools and bath water, etc. Mounting evidence has indicated that IAA could act as a reproductive toxicant and bring about multifarious adverse reproductive damage. For instance, it can interfere with gonadal development, weaken ovarian function, impair sperm motility, trigger DNA damage to germ cells, perturb steroidogenesis, etc. The underlying mechanisms predominantly include cytotoxic and genotoxic effects on germ cells, disturbance of the hypothalamic-pituitary-gonadal axis, oxidative stress, inhibition of steroidogenic proteins or enzymes, and dysbiosis of gut microbiota. Nevertheless, there are still some knowledge gaps and limitations in studying the potential impact of IAA on reproduction, which urgently need to be addressed in the future. We suppose that necessary population epidemiological studies, more sensitive detection methods for internal exposure, and mechanism-based in-depth exploration will contribute to a more comprehensive understanding of characteristics and biological effects of IAA, thus providing an important scientific basis for revising sanitary standards for drinking water quality.